Endocytosis: a pivotal pathway for regulating metastasis - Khan, Imran; Steeg, Patricia S. (British journal of cancer, 2021)
A potentially important aspect in the regulation of tumour metastasis is endocytosis. This process consists of internalisation of cell-surface receptors via pinocytosis, phagocytosis or receptor-mediated endocytosis, the latter of which includes clathrin-, caveolae- and non-clathrin or caveolae-mediated mechanisms. Endocytosis then progresses through several intracellular compartments for sorting and routing of cargo, ending in lysosomal degradation, recycling back to the cell surface or secretion. Multiple endocytic proteins are dysregulated in cancer and regulate tumour metastasis, particularly migration and invasion. Importantly, four metastasis suppressor genes function in part by regulating endocytosis, namely, the NME, KAI, MTSS1 and KISS1 pathways. Data on metastasis suppressors identify a new point of dysregulation operative in tumour metastasis, alterations in signalling through endocytosis. This review will focus on the multicomponent process of endocytosis affecting different steps of metastasis and how metastatic-suppressor genes use endocytosis to suppress metastasis.